Media Pembelajaran Sejarah Dalam Kurikulum 2013 - Yetty Rahelly (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2015)
The development of science and technology increasingly encourages reform efforts in the utilization of technology in the learning process. The teachers are required to be able to use the tools that are in accordance with the developments and demands of the times. Teachers are also required to develop the skills to make learning media uses. In 2013 the curriculum in the classroom using a scientific approach. For that teachers should have sufficient knowledge and understanding to make learning media in accordance with the approach scientifik. media is an integral part of the learning process for the achievement of the goals of education in general and in particular the purpose of teaching history.